Waste wood as bioenergy feedstock. Climate change impacts and related emission uncertainties from waste wood based energy systems in the UK. (April 2018) - Röder, Mirjam; Thornley, Patricia
Highlights: Emission from energy from waste wood in different applications are evaluated. Sensitivity analyses of transport, pelletizing, wood processing and resins fraction. Largest emission uncertainties are related to urea resins and potential N2 O formation. Feedstocks with low contamination levels provide valuable GHG mitigation options. Low grade feedstocks only achieve reductions when replacing highly carbon intense fuels. Abstract: Considering the urgent need to shift to low carbon energy carriers, waste wood resources could provide an alternative energy feedstock and at the same time reduce emissions from landfill. This research examines the climate change impacts and related emission uncertainties of waste wood based energy. For this, different grades of waste wood and energy application have been investigated using lifecycle assessment. Sensitivity analysis has then been applied for supply chain processes and feedstock properties for the main emission contributing categories: transport, processing, pelletizing, urea resin fraction and related N2 O formation. The results show, depending on the waste wood grade, the conversion option, scale and the related reference case, that emission reductions of up to 91% are possible for non-treated wood waste. Compared to this, energy from treated wood waste with low contamination can achieve up to 83% emission savings, similar to untreated waste wood pellets, but in some cases emissions from waste wood based energy can exceed the ones of the fossil fuel reference - in the worst case by 126%. Emission reductions from highly contaminated feedstocks are largest when replacing electricity from large-scale coal and landfill. The highest emission uncertainties are related to the wood's resin fraction and N2 O formation during combustion and, pelletizing. Comparing wood processing with diesel and electricity powered equipment also generated high variations in the results, while emission variations related to transport are relatively small. Using treated waste wood as a bioenergy feedstock can be a valid option to reduce emissions from energy production but this is only realisable if coal and landfill gas are replaced. To achieve meaningful emission reduction in line with national and international climate change targets, pre-treatment of waste wood would be required to reduce components that form N2 O during the energy conversion.